Synthesis and characterization of corrosion protective poly(2,5-dimethylaniline) coatings on copper - Shinde, Vandana; Gaikwad, A. B.; Patil, P. P. (Applied Surface Science, 2006)
Poly(2,5-dimethylaniline) coatings were synthesized on copper (Cu) by electrochemical polymerization of 2,5-dimethylaniline in aqueous salicylate solution by using cyclic voltammetry. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of 2,5-dimethylaniline to generate strongly adherent and smooth poly (2,5-dimethylaniline) coatings on Cu substrates. The performance of poly(2,5-dimethylaniline) as protective coating against corrosion of Cu in aqueous 3% NaCl was assessed by the potentiodynamic polarization technique. The results of the potentiodynamic polarization demonstrate that the poly(2,5-dimethylaniline) coating has ability to protect the Cu against corrosion. The corrosion potential was about 0.078 V versus SCE more positive in aqueous 3% NaCl for the poly(2,5-dimethylaniline) coated Cu than that of uncoated Cu and reduces the corrosion rate of Cu almost by a factor of 31. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 5-dimethylaniline) coatings; conducting polymers; Copper; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; Poly(2

Synthesis of corrosion inhibitive poly(2,5-dimethylaniline) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Gangal, S. A.; Patil, P. P. (Journal of Materials Science, 2006)
An attempt has been made towards the synthesis of strongly adherent poly(2,5-dimethylaniline) coatings on low carbon steel substrates, with an objective of examining the possibility of using this polymer for corrosion protection of steel in chloride environment. In this work, the poly(2,5-dimethylaniline) coatings were synthesized by electrochemical polymerization of 2,5-dimethylaniline using sodium salicylate as a supporting electrolyte. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy. The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of 2,5-dimethylaniline to generate strongly adherent and smooth poly(2,5-dimethylaniline) coatings on low carbon steel substrates. The performance of poly(2,5-dimethylaniline) as protective coating against corrosion of low carbon steel in aqueous 3% NaCl was assessed by the open circuit potential and the potentiodynamic polarization measurements. The potentiodynamic polarization measurement reveals that the poly(2,5-dimethylaniline) coating increases the corrosion potential and reduces the corrosion rate of low carbon steel almost by a factor of 50. This study clearly ascertains that the poly(2,5-dimethylaniline) has outstanding capability to protect low carbon steel against corrosion in chloride environment. (c) 2006 Springer Science + Business Media, Inc.

Studies on gas sensing performance of pure and modified barium strontium titanate thick film resistors - Jain, G. H.; Patil, L. A.; Patil, P. P.; Mulik, Uttam P.; Patil, K. R. (Bulletin of Materials Science, 2007)
Barium strontium titanate ((Ba0.87Sr0.13)TiO3-BST) ceramic powder was prepared by mechanochemical process. The thick films of different thicknesses of BST were prepared by screen-printing technique and gas-sensing performance of these films was tested for various gases. The films showed highest response and selectivity to ammonia gas. The effect of film thickness on gas response was also studied. As prepared BST thick films were surface modified by dipping them into an aqueous solution of titanium chloride (TiCl3) for different intervals of time. Surface modification shifted response to H2S gas suppressing the responses to ammonia and other gases. The surface modification, using dipping process, altered the adsorbate-adsorbent interactions, which gave the unusual sensitivity and selectivity effect. Sensitivity, selectivity, thermal stability, response and recovery time of the sensor were measured and presented.
Keywords: (Ba0.87Sr0.13)TiO3 thick films; ammonia gas sensor; II2S gas sensor; selectivity; sensitivity

Synthesis and LPG sensing properties of nano-sized cadmium oxide - Waghulade, R. B.; Patil, P. P.; Pasricha, Renu (Talanta, 2007)
This paper reports the synthesis and liquid petroleum gas (LPG) sensing properties of nano-sized cadmium oxide (CdO). The nano-sized CdO powder was successfully synthesized by using a chemical co-precipitation method using cadmium acetate and the ammonium hydroxide, as starting materials and water as a carrier. The resulting nano-sized powder was characterized by X-ray diffraction (XRD) measurements and the transmission electron microscopy (TEM). The LPG sensing properties of the synthesized nano-sized CdO were investigated at different operating temperatures and LPG concentrations. It was found that the calcination temperature and the operating temperature significantly affect the sensitivity of the nano-sized CdO powder to the LPG. The sensitivity is found to be maximum when the calcination temperature was 400 degrees C. The sensitivity to 75 ppm of LPG is maximum at an operating temperature 450 degrees C and it was found to be similar to 34 1 %. The response and recovery times were found to be nearly 3-5s and 8-10s, respectively. The synthesized nano-sized CdO powder is able to detect up to 25 ppm for LPG with reasonable sensitivity at an operating temperature 450 degrees C and it can be reliably used to monitor the concentration of LPG over the range (25-75 ppm). The experimental results of the LPG sensing studies reveal that the nano-sized CdO powder synthesized by a simple co-precipitation method is a suitable material for the fabrication of the LPG sensor. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chemical co-precipitation; Gas sensor; LPG; nano-sized CdO

Synthesis of poly(aniline-co-o-toluidine) coatings and their corrosion-protection performance on low-carbon steel - Pawar, Pritee; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2007)
Strongly adherent poly(aniline-co-o-toluidine) coatings were synthesized on low-carbon-steel substrates by the electrochemical copolymerization of aniline with o-toluidine with sodium tartrate as the supporting electrolyte. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, and scanning electron microscopy. The formation of the copolymer with the mixture of monomers in the aqueous sodium tartrate solution was ascertained by a critical comparison of the results obtained from the polymerizations of the individual monomers, aniline and o-toluidine. The optical absorption spectrum of the copolymer was drastically different from the spectra of the respective homopolymers, polyaniline and poly(o-toluidine). The extent of the corrosion protection offered by poly(aniline-co-o-toluidine) coatings to low-carbon steel was investigated in aqueous 3% NaCl solutions by open-circuit-potential measurements and a potentiodynamic polarization technique. The results of the potentiodynamic polarization measurements showed that the poly(aniline-co-o-toluidine) coatings provided more effective corrosion protection to low-carbon steel than the respective homo-polymers. The corrosion rate depended on the feed ratio of o-toluidine used for the synthesis of the copolymer coatings. (c) 2006 Wiley Periodicals, Inc.
Keywords: Coatings; conducting polymers; copolymerization; synthesis

Synthesis and corrosion protection study of poly(o-ethylaniline) coatings on copper - Shinde, Vandana; Gaikwad, A. B.; Patil, P. P. (Surface & Coatings Technology, 2008)
Poly(o-ethylaniline) coatings were synthesized on copper (Cu) by electrochemical polymerization of o-ethylaniline in an aqueous salicylate solution by using cyclic voltammetry. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-ethylaniline to generate strongly adherent and smooth poly(o-ethylaniline) coatings on Cu substrates. The performance of poly(o-ethylaniline) as protective coating against corrosion of Cu in aqueous 3% NaCl was assessed by the potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of these studies demonstrate that the poly(o-ethylaniline) coating has ability to protect the Cu against corrosion. The corrosion potential was about 0.078 V versus SCE more positive in aqueous 3% NaCl for the poly(o-ethylanitine) coated Cu (similar to 15 mu m thick) than that of uncoated Cu and reduces the corrosion rate of Cu almost by a factor of 70. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: conducting polymers; Copper; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; poly(o-ethylaniline) coatings

Synthesis and corrosion protection aspects of poly(o-toluidine)/CdO nanoparticle composite coatings on mild steel - Chaudhari, Sudeshna; Gaikwad, A. B.; Patil, P. P. (Journal of Coatings Technology and Research, 2010)
This study examines the possibility of using poly(o-toluidine)/CdO (POT-CdO) nanoparticle composite coating for corrosion protection of mild steel in chloride environment. The POT-CdO nanoparticle composite coating was synthesized on mild steel from aqueous tartrate solution containing CdO-nanoparticles (size similar to 18 nm) by using cyclic voltammetry. These coatings were characterized by cyclic voltammetry, UV-Visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray diffraction measurements. The corrosion protection aspects of the resulting POT-CdO nanocomposite structure were investigated in aqueous 3% NaCl solution by potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of these investigations reveal that the POT-CdO nanoparticle composite acts as a protective coating on mild steel and reduces the corrosion rate of mild steel almost by factor of 70.
Keywords: CdO; Conducting polymer coatings; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; Mild steel; Nanocomposites; Poly(o-toluidine)